Current Account Dynamics, Adjustment and Capital Mobility in Bangladesh - Alam, Mohammad Masud; Khondker, Rezai Karim; Molla, Mohammad Shahansha (Global Disclosure of Economics and Business, 2013)
This paper examines current account (CA) dynamics, its relationship with the degree of capital mobility and the state of integration of the Bangladesh capital market with the global capital market. For the period 1976-2012, findings of AR (1) process shows a rigid CA position along with its slow adjustment and its inflexibility against real shocks, lower degree of capital mobility and a slow progress of capital market integration with the rest of the world. Compared to the period of fixed exchange rate regime, lesser degree of  rigidity has been observed during the flexible exchange rate period suggesting a smooth and flexible current account position; but shows an increased degree of rigidity and capital immobility for the overall time period under consideration. These findings reveal some important policy implications in respects of current and capital account liberalization, deregulation of domestic markets and removing entry barriers on the part of Bangladesh to boost up FDI and remittance inflows.